PELATIHAN PENGOLAHAN AIR KELAPA MENJADI KECAP DI DESA MATTIRODECENG, KECAMATAN TIROANG, KABUPATEN PINRANG - Natsir, Hasnah; Arif, Abdur Rahman; Arfah, Rugaiyah A; Zakir, Muhammad; St Fauziah, St Fauziah; Budi, Prastawa (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
Mattirodeceng is a village located in Pinrang Regency, which has considerable natural resource potential in coconut production. But the utilization of coconut plants, especially the water of coconut, is still low. Coconut water only used for consumption purposes at certain times. The purpose of this activity is to provide training on the benefits and ways of processing coconut water into soy sauce for PKK groups in the Mattirodeceng village. The method used in this activity consisted of the pre-activity stage, which included a survey of the location and trial making of soy sauce made from coconut water. The implementation of activities carried out by counseling methods and training on the benefits and ways of processing coconut water into soy sauce. The result of the application of this activity was an increase in participants' knowledge about coconut water, namely its nutritional content, and its processed products in the form of soy sauce. The Organoleptic test showed the level of panelists' preference for taste, flavour, texture, and color showed good results, where all panelists liked the coconut water soy sauce products Keywords: Coconut water, soy sauce, organoleptic Mattirodeceng Village. ABSTRAK Mattirodeceng merupakan salah satu desa yang terletak di Kabupaten Pinrang yang memiliki potensi sumber daya alam yang cukup besar dalam produksi kelapa. Namun pemanfaatan tanaman kelapa, terutama air kelapa masih rendah. Air kelapa hanya digunakan untuk keperluan konsumsi pada saat-saat tertentu. Tujuan dari kegiatan ini yaitu untuk memberikan pelatihan manfaat dan cara pengolahan air kelapa menjadi kecap kepada kelompok PKK di desa mattirodeceng. Metode yang digunakan dalam kegiatan ini terdiri dari tahap pra kegiatan yang meliputi survei lokasi dan uji coba pembuatan kecap air kelapa. Tahap pelaksanaan kegiatan dengan metode penyuluhan dan pelatihan tentang manfaat serta cara pengolahan air kelapa menjadi kecap. Hasil dari pelaksanaan kegiatan ini adalah meningkatnya pengetahuan peserta tentang air kelapa, yaitu kandungan gizinya, dan produk olahannya berupa kecap. Hasil uji organoleptik menunjukkan tingkat kesukaan panelis terhadap rasa, aroma, tekstur dan warna menunjukkan hasil yang baik, dimana seluruh panelis menyukai produk kecap air kelapa. Kata kunci: Air kelapa, kecap, organoleptik, Desa Mattirodeceng.